The Ritual (Traditional) Songs In The Villages Of Tirana - Duqi, Kreshnik (European Scientific Journal, ESJ, 2016)
This work intends to reflect on and to analyze the rituals ever-present during the holidays and the traditional celebrations during the year. The stimulus for this study was the interest shown towards ritual songs, which with the passing of the time are being forgotten and fade away as a result of social and cultural development. In this study we intend to point out some general characteristics of the songs of the spring season, including important holidays and rituals such as: “The First day of Summer”, “Llazoret (collecting eggs from the neighbors as a sign of spring coming)”, “Saint George”, etc; and also other songs which represent the traditional rituals related to agriculture and livestock farming to whom are dedicated specific ceremonies too. In this study we have analyzed some of these songs in order to better understand their origin and to reach some conclusions too. We found out that the song “Llazoret” is sung in different areas of Tirana’s villages, but with some variations. The grouping of the songs used in this study testifies that the origin of these songs is very old. Outside the rituals these songs lost their original meaning and that’s the reason why many of them are disappeared and the rest is dying slowly because of the obliteration.